Genomic relationships between hexaploid Helianthus resinosus and diploid Helianthus annuus (Asteraceae) - Miranda Zanetti, Julieta; Greizerstein, Eduardo Jose; Camadro, Elsa Lucila; Poverene, María Mónica; Echeverria, Mercedes; Poggio, Lidia; Carrera, Alicia Delia (Springer, 2018)
Genus Helianthus comprises diploid and polyploid species. An autoallopolyploid origin has been proposed for hexaploid species but the genomic relationships remain unclear. Mitotic and meiotic studies in annual Helianthus annuus (2n = 2x = 34) and perennial Helianthus resinosus (2n = 6x = 102) as well as the F1 hybrids between both species were carried out. Chromosome counting confirmed the hybrid origin of the latter plants and their tetraploid condition. Bivalents in hybrids ranged from 12 to 28 ( x¯ = 20.8). Univalents, trivalents and quadrivalents were also observed. Meiotic products comprised dyads, triads and normal tetrads and pollen grains were heterogeneous in size. These observations suggest the occurrence of 2n pollen in addition to the expected n. Genomic in situ hybridization (GISH) of total H. annuus DNA on H. resinosus chromosomes rendered weak but uniform signals; similar hybridization pattern was observed using three other annual species. Hybridization with H. annuus probe performed on root tip cells of F1 H. annuus × H. resinosus hybrids revealed 17 chromosomes with a strong hybridization signal. GISH in hybrid meiocytes distinguished chromosomes from parental species and revealed autosyndetic pairing of H. resinosus chromosomes, allosyndetic pairing in bivalents, trivalents and quadrivalents, and the presence of univalents derived from parents, H. annuus and H. resinosus. Results obtained from classical and molecular cytogenetics do not support H. annuus as a direct ancestor of H. resinosus. The occurrence of allosyndetic pairing and the relatively high fertility of the F1 hybrids point to the possibility that useful genes could be transferred from H. resinosus to cultivate sunflower, although the effective rate of recombination has not been evaluated. GISH method proved effective to recognize parental chromosomes in H. annuus × H. resinosus progeny.